Three administrative texts from the time of the Third Dynasty of Ur in an anonymous collection in Poland - Stępień, Marek; Drewnowska, Olga (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2021)
The article is a full edition (photography, autography, transliteration, translation and commentary) of three previously unpublished Neo-Sumerian administrative documents, held in one of the anonymous collections in Poland. The tablets come from two provincial archives of the kingdom of the Third Dynasty of Ur, Puzriš-Dagan and Girsu-Lagaš, and their content is typical of this group of cuneiform texts.